Van Wijk’s law and questions of relative chronology - Kortlandt, Frederik (Baltistica, 2019)
Babik rejects Van Wijk’s law on the basis of such forms as *volja ‘will’, *melje–‘grind’, *gorje ‘worse’ because he would expect metathesis in these words if *j was an ordinary consonant. Since the rise of geminates preceded the metathesis of liquids, the assumption is fallacious.Babik thinks that in my view, the lengthening before tautosyllabic liquids was concomitant with the metathesis in Ce/oRC sequences. This is incorrect.